THE VALUE OF STRATEGIC ALLIANCES FOR RAILWAYS SUPPORT - Hricova, Romana (Doprava a spoje, 2011)
The paper deals with the concept and effort to establish strategic pro-rail alliance in Slovakia. It provides the basic ideas about aims, potential members, financial sources acquisition and target groups. It shows the scope of activities that can be addressed under the frame of alliance. The concept was done on the base of adoption the FLAVIA project partner Allianz pro Schiene methodology.